Swapping Mallards: Monocular imprints in ducklings are unavailable to the opposite eye - Martinho, A; Kacelnik, A (Elsevier, 2016)
Eutherian mammals are unique in that sensory input from each eye is exchanged and shared between left and right brain hemispheres through the corpus callosum. All other vertebrates lack this structure and hence interocular information exchange is more restricted, raising issues of how information acquired with each eye contributes to the control of behaviour. Studies of food hoarding, laboratory discrimination, and homing in birds show that information acquired with one eye is not immediately available for action guided by the opposite one. We investigate interocular transfer, using filial imprinting in ducklings as experimental system. In Experiment 1 we imprinted hatchlings on either of two duck decoys, in three treatments differing on whether (A) birds were trained and later tested for a following response binocularly, (B) trained and tested monocularly, with the same eye, or (C) trained and tested monocularly, with opposite eyes. Birds preferred the training decoy for at least 3 hours after imprinting in treatments A and B, but were indifferent in C. In Experiment 2 birds were imprinted sequentially with two decoys, in three treatments where they were (D) trained and tested binocularly, (E) trained monocularly with a different decoy for each eye and tested monocularly with each eye, or (F) trained monocularly with a different decoy for each eye and tested binocularly. In treatment D ducklings were close to indifference, with a weak preference for the most recent decoy. In treatment E preference weakly favoured the decoy used during imprinting with the eye being tested. Finally, in treatment F there was no evidence for dominance of either eye. Thus, imprinting information is laterally isolated for at least three hours, the experience status of the opposite eye (naïve or with a competing imprinting) has a small effect, and we found no evidence for eye dominance.